2015
DOI: 10.17795/compreped-20587
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Exchange Transfusion in Hospitalized Neonates in Two Neonatal Centers in Hamadan, A Five-Year Experience

Abstract: Background: Exchange transfusion is commonly used in newborns for immediate treatment of severe hyperbilirubinemia to prevent bilirubin encephalopathy and kernicterus. Objectives: This study aimed to determine etiology and complications in newborns who received exchange transfusion for severe hyperbilirubinemia over the last five years. Patients and Methods: A retrospective study was performed on 28 days old infants who received exchange transfusion due to severe hyperbilirubinemia for a period of five years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
1
14
1
Order By: Relevance
“…Satyasree (2017) found in their study that there were 61.1% males and 38.8% females who had neonatal jaundice. 9 The present study is antithetical to the findings of Sabzehei et al (2015) 10 who found that among 148 neonates, 80 (54.9%) were female Rahman et al (2015) found 16 (41%) cases were male and 23 (59%). 11 Sex-wise changes in hematological and biochemical parameters before and after exchange transfusion in males and females:…”
Section: Discussionsupporting
confidence: 87%
“…Satyasree (2017) found in their study that there were 61.1% males and 38.8% females who had neonatal jaundice. 9 The present study is antithetical to the findings of Sabzehei et al (2015) 10 who found that among 148 neonates, 80 (54.9%) were female Rahman et al (2015) found 16 (41%) cases were male and 23 (59%). 11 Sex-wise changes in hematological and biochemical parameters before and after exchange transfusion in males and females:…”
Section: Discussionsupporting
confidence: 87%
“… 1 Kernicterus or bilirubin encephalopathy is caused by unconjugated hyperbilirubinemia that develops either as a result of hemolytic process or because of the inability of the liver to conjugate bilirubin. 2 The risk of mortality and severe long-term neurodevelopmental sequelae due to severe hyperbilirubinemia is high in low- and middle-income country like Bangladesh. The burden is likely to be exacerbated by lack of poor or timely access to proven therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Complication occurred in 57 (38.5%) neonates and the most common complications were thrombocytopenia in 26 (17.6%) and hypocalcemia in 17 (11.5%) neonates. 22 In this case, patient had jaundice since the first day of life and become progressively increased accompanied by LAPSUS neurologic disorder. His laboratory result showed high level of total bilirubin and indirect bilirubin so we did exchange transfusion.…”
Section: Discussionmentioning
confidence: 76%